ANALISIS SEKTOR EKONOMI BASIS TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TIMUR (PENDEKATAN INPUT-OUTPUT) - Juansyah, Dhemmi; Jumiati, Aisah; Lestari, Endah Kurnia (UPT Penerbitan Universitas Jember, 2024)
Base sector is an economic sector thet serve the market’s demand in the region and outside the region. Location Quotient analysis tool is needed to seek the base economic sector in East Java Province. After that, The base sector will be analyzed using analytical tools like direct forward linkage, direct backward linkage, output multiplier and income multiplier. The result of this research are Manufacturing Sector; Wholesale and Retail Trade, Repair of Motor Vehicles and Motorcyles Sector; and Transportation Sector is the base sector in East Java Province. Through linkage impact, The three base sectors in East Java Province have an important role in increasing the output of other economic sectors. Through multiplier effect the three basic sectors of East Java Province contributed greatly to output growth and increased household income.